The Construction of Multiple Cultural Identities of Cross-border Intermarriage Families: A Case Study of Luangnamtha Province Laos and Mengla China - Xaysamone, Latsamy (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study examines the construction of multiple cultural identities among cross-border intermarriage families in Luangnamtha Province, Laos, and Mengla County, China. Situated along the China–Laos border, this region has long been characterized by historical mobility, ethnic continuity, and cross-border kinship networks. In recent years, cross-border marriage has become increasingly common, significantly shaping demographic structures, family life, and identity formation. Using a qualitative case study approach supported by government records from 2018 to 2023, this research analyzes patterns of marriage, gender roles, legal status, and intergenerational experiences within transnational households. The findings reveal a steady rise in registered cross-border marriages in both regions, with particularly high prevalence among ethnic minority groups such as the Tai Lue, Akha, and Hmong. Most marriages involve Lao women marrying Chinese men, reflecting demographic imbalances and economic disparities between the two areas. After marriage, women typically relocate to China and assume domestic roles, reinforcing traditional gender expectations. At the same time, a large proportion of these women lack secure legal status, limiting their access to citizenship rights, social welfare, and employment opportunities. The growing number of children born into cross-border families further highlights issues related to nationality, education, and access to public services. Despite these challenges, cross-border households also function as dynamic spaces of cultural exchange, where language, customs, and traditions from both countries are negotiated and blended in everyday life. This research contributes to broader discussions on transnational families, cultural hybridity, and borderland identity in Southeast Asia. It demonstrates that cultural identity in cross-border contexts is not fixed but continuously constructed through daily practices shaped by both intimate relationships and state structures.